2005
DOI: 10.1097/00004356-200509000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Development of an exercise testing protocol for patients with a lower limb amputation: results of a pilot study

Abstract: Due to a decrease in physical activity, lower limb amputees experience a decline in physical fitness. This causes problems in walking with a prosthesis because energy expenditure in walking with a prosthesis is much higher than in walking with two sound legs. Exercise training may therefore increase the functional walking ability of these patients. To generate a safe and effective aerobic training program, exercise testing of amputees is recommended. The objectives of this study were to develop a maximal exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 13 publications
(12 reference statements)
2
18
1
Order By: Relevance
“…The maximal oxygen uptake during the exercise testing was 12.1 ml/kg/min on average, while the mean proportion of age-adjusted normative oxygen uptake at maximum exercise power was 57.5%. This makes our study comparable to previous similar research [7,33,36].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The maximal oxygen uptake during the exercise testing was 12.1 ml/kg/min on average, while the mean proportion of age-adjusted normative oxygen uptake at maximum exercise power was 57.5%. This makes our study comparable to previous similar research [7,33,36].…”
Section: Discussionsupporting
confidence: 91%
“…At our rehabilitation hospital, exercise testing has therefore been included into the clinical pathway for all the patients after transfemoral amputation due to PVD. Despite some initial doubts [32], hand-wheel ergometry without direct gas analyses has been proven to be a reliable, repeatable and safe method that provides data on physical fitness, heart rhythm problems, hypertensive response to strain and possible low-threshold angina pectoris in ischaemic heart disease [5,26,33]. Rather than using direct gas measurement, we decided to calculate the maximal oxygen uptake according to the ACSM formula [26] because breathing through the mask could pose an unreasonable risk for those in poor physical condition and at high risk for cardiovascular events during exercise testing.…”
Section: Discussionmentioning
confidence: 99%
“…e.g. 2,3,4,5 Using mainly test protocols based on one-leg cycle ergometry or upper body ergometry, these studies collectively report very low VO2max values compared to predicted values for healthy individuals of the same age and sex. 6 A low level of VO2max for transfemoral amputees (TFA) may be caused by several factors: The VO2max may be systematically underestimated due to the choice of test protocol, i.e.…”
Section: Introductionmentioning
confidence: 98%
“…Vestering et al23 ) similarly found that the combined ergometer test increased the heart rate of lower limb amputees. We found that the heart rate was increased in all our tests indicating that both exercise and addition of weight increases the heart rate.…”
Section: Discussionmentioning
confidence: 92%